Korespondesi Bunyi Bahasa Aceh dan Bahasa Gayo - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
AbstractAcehnese and Gayonese belong to Austronesian languages which are cognate genetically. Adjacent location became the basis for the assumption that both language are related one of the linguistic kinship indicators described in comparative historical linguistic studies in occurrence of sound changes that occur regularly. The two languages show similar specific features. One of them is a phenomenon of sound changes that is called a phonemic correspondence. The sound changes in the two languages happen continuously. In this paper, the writer wants to prove the cognate phenomenon by using a comparative analysis, especially by applying a phonemic correspondence technique. Based on similarities in form and correspondence phonemes technique, it was found that the formula of the phonemic correspondence in Acehnese and Gayonese are: *a and *u> in phonemic correspondence /a e/, /a o/, /o u/, and /e u/ especially on position penultima bilabial, palatal, dorsovelar, and faringal.IntisariBahasa Aceh dan bahasa Gayo merupakan bahasa Austronesia yang secara genetis bersifat kognat. Letak yang berdekatan menjadi dasar asumsi kedua bahasa tersebut kekerabatan. Salah satu indikator kekerabatan bahasa yang dijelaskan dalam kajian linguistic historis komparatif yakni adanya perubahan bunyi bahasa yang terjadi secara teratur. Hal ini ditunjukan oleh okurensi perubahan bunyi yang disebut korespondensi fonemis. Perubahan bunyi bahasa Aceh dan bahasa Gayo terjadi secara konstan dan teratur pada setiap segmen dari glos yang dibandingkan. Berdasar pada kesamaan bentuk dan makna, dengan menggunakan teknik korespondensi fonemis, diperoleh formula korespondensi fonemis dalam bahasa Aceh dan bahasa Gayo sebagai berikut: *a dan *u > memiliki korespondensi fonemis /a e/, /a o/, /o u/, dan /e u/ terutama pada posisi penultima bilabial, palatal, dorsovelar, dan faringal.